Higher Trace Elements and Lower Fatty Acids Levels in Erythrocytes as Predictors of Preeclampsia - Putri, Ruth Widhiati Raharjo; Prasmusinto, Damar; Wibowo, Noroyono; Irwinda, Rima; Purwosunu, Yuditiya; Saroyo, Yudianto Budi (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: Preeclampsia is one of the common causes of maternal death in Indonesia. Many studies only focus on the diagnosis and pharmacological treatment of preeclampsia. However, predictors of preeclampsia need to be observed to add more focus on the etiology and prevention of preeclampsia. The imbalances of trace elements and fatty acids play an important role in preeclampsia. Therefore, this study was conducted to evaluate the status of trace elements and fatty acids in preeclampsia patients as predictors of preeclampsia.METHODS: A cross-sectional study was conducted in 3 hospitals, and involving 40 pregnant women classified into severe preeclampsia and normotensive groups. Trace elements and fatty acids were measured in serum and erythrocytes using Inductively Coupled Plasma and Gas Chromatography-Mass Spectrometry. Serum and erythrocytes fatty acid levels' cut-off value, sensitivity, and specificity were analyzed using Receiver Operating Characteristic (ROC) curve and Area Under the Curve (AUC) value.RESULTS: Serum selenium, manganese, and iron levels were significantly different in the preeclampsia group than in the controls (p<0.05). Of all the heavy metals, higher concentrations of cadmium, arsenic, lead, and mercury were found in preeclampsia groups compared to control. Linoleic acid showed the highest predictive value to increase severe preeclampsia with AUC of 0.8. The ratio of high omega-6/omega-3 increases the risk of preeclampsia.CONCLUSION: Selenium, manganese, iron, cadmium, arsenic, lead, and mercury levels are higher in the serum of preeclampsia patients. Almost all erythrocyte fatty acids were significantly higher in the control group compared to preeclampsia. Measurement of trace elements and fatty acids is needed as a predictor of preeclampsia. Erythrocyte fatty acids measurement is considered better than serum.KEYWORDS: trace elements, fatty acids, preeclampsia